Multiple Disruptions of Glial-Neuronal Networks in Epileptogenesis That Follows Prolonged Febrile Seizures - Brennan, Gary P.; Garcia-Curran, Megan M.; Patterson, Katelin P.; Luo, Renhao; Baram, Tallie Z. (Frontiers in Neurology, 2021)
Background and Rationale: Bi-directional neuronal-glial communication is a critical mediator of normal brain function and is disrupted in the epileptic brain. The potential role of aberrant microglia and astrocyte function during epileptogenesis is important because the mediators involved provide tangible targets for intervention and prevention of epilepsy. Glial activation is intrinsically involved in the generation of childhood febrile seizures (FS), and prolonged FS (febrile status epilepticus, FSE) antecede a proportion of adult temporal lobe epilepsy (TLE). Because TLE is often refractory to treatment and accompanied by significant memory and emotional difficulties, we probed the role of disruptions of glial-neuronal networks in the epileptogenesis that follows experimental FSE (eFSE). Methods: We performed a multi-pronged examination of neuronal-glia communication and the resulting activation of molecular signaling cascades in these cell types following eFSE in immature mice and rats. Specifically, we examined pathways involving cytokines, microRNAs, high mobility group B-1 (HMGB1) and the prostaglandin E2 signaling. We aimed to block epileptogenesis using network-specific interventions as well as via a global anti-inflammatory approach using dexamethasone. Results: (A) eFSE elicited a strong inflammatory response with rapid and sustained upregulation of pro-inflammatory cytokines. (B) Within minutes of the end of the eFSE, HMGB1 translocated from neuronal nuclei to dendrites, en route to the extracellular space and glial Toll-like receptors. Administration of an HMGB1 blocker to eFSE rat pups did not decrease expression of downstream inflammatory cascades and led to unacceptable side effects. (C) Prolonged seizure-like activity caused overall microRNA-124 (miR-124) levels to plunge in hippocampus and release of this microRNA from neurons via extra-cellular vesicles. (D) Within hours of eFSE, structural astrocyte and microglia activation was associated not only with cytokine production, but also with activation of the PGE2 cascade. However, administration of TG6-10-1, a blocker of the PGE2 receptor EP2 had little effect on spike-series provoked by eFSE. (E) In contrast to the failure of selective interventions, a 3-day treatment of eFSE–experiencing rat pups with the broad anti-inflammatory drug dexamethasone attenuated eFSE-provoked pro-epileptogenic EEG changes. Conclusions: eFSE, a provoker of TLE-like epilepsy in rodents leads to multiple and rapid disruptions of interconnected glial-neuronal networks, with a likely important role in epileptogenesis. The intricate, cell-specific and homeostatic interplays among these networks constitute a serious challenge to effective selective interventions that aim to prevent epilepsy. In contrast, a broad suppression of glial-neuronal dysfunction holds promise for mitigating FSE-induced hyperexcitability and epileptogenesis in experimental models and in humans.